Adverse events associated with herbal medicine products reported in the Korea Adverse Event Reporting System from 2012 to 2021 - Choi, Yujin; Shin, Hyeun-Kyoo (Frontiers in Pharmacology, 2024)
Introduction: Systematic collection of diverse adverse events during herbal medicine administration is crucial. The Korea Adverse Event Reporting System (KAERS) compiles spontaneously reported adverse event data for medicinal products including herbal medicines. This study focused on extracting and analyzing adverse event data specifically related to herbal medicine products from the KAERS database.Methods: Individual case safety reports (ICSRs) encompassing 84 types of herbal medicine products, identified by item codes from 2012 to 2021, were extracted from the KAERS database. Descriptive statistics were employed to analyze the characteristics of the extracted reports, and adverse event information was systematically categorized and analyzed based on the MedDRA System Organ Class and preferred term classification.Results: In total, 1,054 ICSRs were extracted, with some documenting multiple adverse events in a single ICSR, resulting in 1,629 extracted adverse events. When categorized by the MedDRA System Organ Class, gastrointestinal disorders were the most prevalent (28.7%), followed by skin and subcutaneous tissue disorders (20.1%). Based on the preferred terms, the most frequently reported adverse events were diarrhea (5.8%), urticaria (5.3%), pruritus (4.7%), rash (4.4%), and abdominal discomfort (4.2%). The most frequently reported herbal medicines were Bangpungtongseong-san (297 cases), Kyeongok-go (144 cases), and Eunkyo-san (108 cases).Spontaneously reported adverse events associated with herbal medicine products were systematically documented using the KAERS database. This study, which focused on voluntarily reported adverse reactions, underscores the need for additional research to estimate the incidence rate of adverse events and assess causality.